Peran Self-Compassion sebagai Mediator antara Dimensi Attachment dan Kualitas Hubungan Pacaran Dewasa Muda - Angela, Irene; setiasih, setiasih (Universitas Islam Indonesia, 2023)
Dating relationship is time for individual get to know his partner before decide to get married or not. Therefore, dating relationship quality become important because poor dating relationship quality can negatively affect marital relationship quality. Prior researcher found that individual’s attachment can affect dating relationship quality and self-compassion can mediated attachment and relationship quality. The mechanism of attachment effect was also found to be mediated by self-compassion but this still needs further investigation. The objective of this research is to examine the role of self-compassion in mediating attachment and relationship quality. This research uses quantitative research method by distributing online questionnaire. Total participant of this research is 176 people. Mediation analysis in this research using PROCESS within SPSS. The result of this research shows that self-compassion cannot mediating attachment and dating relationship quality. In other words, individual’s behavior toward himself did not affect individual’s perception toward his relationship or his partner. The next researchers are suggested to do dyadic research, analyses using type of attachment, and examine deeper about self-compassion as the mediator variable.